Large Intra‐Abdominal Abscess Treatment by Marsupialization in 2 Alpacas. Issue 8 (11th September 2014) - Rodvold, Rebecca; Mendez‐Angulo, Jose L.; Firshman, Anna M.; Malone, Erin; Nicholson, Anne
<x xml:space="preserve">Abstract</x> Objectives To report the clinical signs, diagnostic findings, surgical treatment, postoperative complications, and long‐term outcome in 2 adult alpacas with large intra‐abdominal abscesses treated by marsupialization of the abscess to the ventral body wall. Study Design Clinical report. Animals Alpacas (n = 2). Methods Two alpacas each presented with decreased appetite, lethargy, poor body condition, and marked abdominal distension. A complete physical examination, abdominal radiography, and ultrasonography confirmed the presence of large intra‐abdominal abscesses. Streptococcus equi ssp. zooepidemicus was cultured from the abscess fluid of alpaca 1, and a Gram‐negative bacillus from alpaca 2. Results Both alpacas had exploratory celiotomy with marsupialization of the abdominal abscess to the ventral body wall. Postoperatively, alpacas were administered systemic antibiotics and non‐steroidal anti‐inflammatory drugs, and the abscesses were lavaged for several days. Alpaca 2 required a second surgical procedure. The abscesses ultimately resolved in both alpacas, with body wall hernia formation as the only major complication. Both alpacas had good long‐term outcomes. Conclusion Marsupialization to the ventral abdominal wall with concurrent antibiotic treatment should be considered as a treatment option for alpacas with large intra‐abdominal abscesses in which complete surgical resection of the abscess is not possible. An abdominal wall hernia can result from this procedure, and clients should be informed of this potential complication before surgery.